Aktivitas Antibakteri Sari Bawang Putih (Allium Sativum Linn.) Kating Dan Sin Chung Terhadap Pertumbuhan Bakteri Pseudomonas Aeruginosa Perusak Ikan Air Tawar - Windrasari, Cahyani, Pramudya Kurnia, STP, MAgr, Fitriana Mustikaningrum, S.Gz, M.Sc (2016)
Garlic is one of the natural ingredients that has the ability as an antibacterial. Chemical ingredients that has antibacterial properties is allicin. This study was to determine the effect of kating and sin chung garlic (Allium sativum Linn.) concentrate on the inhibition of the growth of Pseudomonas aeruginosa. The type of research is an experimental. The samplings are Pseudomonas aeruginosa, kating and sin chung garlic concentrate with concentrations 0 %, 20 %, 40 %, 60 %. Each treatment is repeated three times. It's statistical test that is used, it is One Way Anova test with p ≤ 0,05 and it is Independent T-test with p ≤ 0,05. Inhibition of Pseudomonas aeruginosa in kating garlic with a concentration of 0%, 20%, 40%, 60% is 0 mm, 1.50 mm, 2.77 mm, 3.94 and sin chung garlic is 0 mm, 1.44 mm, 2.16 mm, 3.27 mm.